2010
DOI: 10.1186/gb-2010-11-9-r94
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and structure of Brassica rapa chromosome A3

Abstract: BackgroundThe species Brassica rapa includes important vegetable and oil crops. It also serves as an excellent model system to study polyploidy-related genome evolution because of its paleohexaploid ancestry and its close evolutionary relationships with Arabidopsis thaliana and other Brassica species with larger genomes. Therefore, its genome sequence will be used to accelerate both basic research on genome evolution and applied research across the cultivated Brassica species.ResultsWe have determined and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 38 publications
4
40
2
Order By: Relevance
“…These assemblies show excellent agreement with 647 BACs 12 and previously assembled chromosome A3 13 (Figure 1), the transposon-related sequences were most abundant in the vicinity of centromeres, inversely related to the abundance of protein-coding genes. We estimated that transposon-related sequences occupy 39.51% of the genome, with the proportions of retrotransposons (with LTRs), DNA transposons and LINEs being 27.14%, 3.20% and 2.82%, respectively (Supplementary Table S3.1T4).…”
Section: Genome Sequence Assembly and Annotationsupporting
confidence: 80%
“…These assemblies show excellent agreement with 647 BACs 12 and previously assembled chromosome A3 13 (Figure 1), the transposon-related sequences were most abundant in the vicinity of centromeres, inversely related to the abundance of protein-coding genes. We estimated that transposon-related sequences occupy 39.51% of the genome, with the proportions of retrotransposons (with LTRs), DNA transposons and LINEs being 27.14%, 3.20% and 2.82%, respectively (Supplementary Table S3.1T4).…”
Section: Genome Sequence Assembly and Annotationsupporting
confidence: 80%
“…Hence, our centromere-positioning analysis suggests that the short arm of chromosome A03 has not been assembled in the published Darmor reference genome. This is not surprising as the short arm of chromosome A03 is a known nucleolar organizing region (NOR), composed of repetitive elements and arrays; Mun et al (2010) were also unable to identify any BACs localized to this chromosome arm in their sequence and assembly of A03. Cheng et al (2013) performed an extensive investigation of paleocentromeres in B. rapa using a sequence-based approach.…”
Section: Discussionmentioning
confidence: 98%
“…A comparison of the B. rapa genome sequence with previously reported linkage maps shows that block D on chromosome A01; blocks W, Q, X, M, and D on A03; S on A05; M, H, and U on A6; F, X, and S on A07; S on A08; K, L, and M on A09; and C on A10 were not detected by genetic mapping (Parkin et al, 2005;Panjabi et al, 2008;Kim et al, 2009;Trick et al, 2009). Although the assembly of B. rapa chromosome A03 by Mun et al (2010) identified 14 GBs or block segments, three additional blocks on the same chromosome were detected within the B. rapa reference genome . Similarly, the 2.4-Mb fragment of block W within the V/K/L/Wa/Q/X association was not detected by genetic mapping.…”
Section: Whole-genome Sequence Assembly Improved the Resolution Of Comentioning
confidence: 99%